From Photos to Performances: Exploring the Digital Transformation of Photovoice Through Velfies - Lucian Ciolan; Loredana Manasia (International Journal of Qualitative Methods)
In response to the challenges posed by the COVID-19 pandemic on traditional Photovoice studies, this article explores the potential of digital technologies to transform the methodology rather than merely adapt it. We introduce velfies (self-recorded video performances), a digital evolution that enhances participant agency by allowing them to shape the research narrative through multimodal and performative elements, such as voice, gesture, and movement. This approach shifts participants from being mere observers to active performers, enriching the research process with diverse, multimodal expressions. Our study with university students, focused on interactions with innovative pedagogies, demonstrates how velfies can deepen engagement and provide richer, more nuanced data. We argue that this performative, digital approach expands Photovoice methodology by bridging the gap between participant experience and researcher interpretation, capturing the complexities of lived educational experiences with greater depth and nuance.